Pengaruh Persepsi Harga dan Kualitas Pelayanan Terhadap Keputusan Penggunaan Ulang Jasa Kontruksi PT Amel Indah Abadi dengan Kepuasan Pelanggan Sebagai Variabel Mediasi - Dandi Suhendra; Aang Curatman; Jefry Romdonny (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The construction service industry plays an important role in economic development. Fierce competition requires companies to maintain prices, service quality, and customer satisfaction. PT. Amel Indah Abadi has experienced project fluctuations, so it is necessary to examine the factors that influence the reuse of its services.This study aims to analyze the effect of price perception and service quality on the decision to reuse construction services with customer satisfaction as a mediating variable. The approach used is quantitative with an explanatory research method. The sample consists of 61 customers of PT. Amel Indah Abadi selected using saturated sampling techniques. Data were collected through a five-point Likert scale questionnaire and analyzed using Partial Least Square (PLS) with the help of SmartPLS 3.0. The results showed that price perception had a positive and significant effect on customer satisfaction (path = 0.477; T = 4.050) and service quality also had a significant effect on customer satisfaction (path = 0.491; T = 4.212). In addition, price perception and service quality have a positive effect on the decision to reuse services (path = 0.387; T = 3.631 and path = 0.305; T = 2.931). Customer satisfaction has a significant effect on the decision to reuse services (path = 0.294; T = 2.726) and significantly mediates the relationship between price perception and service quality on the decision to reuse services (path = 0.140; T = 2.153 and path = 0.144; T = 2.209). The study concluded that reasonable prices and quality service increase satisfaction and encourage repeat use of services. Competitive pricing strategies and service improvements are key to building customer loyalty in the construction sector.